The Impact of Digital Marketing Strategies on Consumer Behavior in Emerging Markets di Sendys Swalayan Kota Palangka Raya - Rita Yuanita Toendan; Hansly Tunjang; Peridawaty; Ina Karuehni (SEULANGA SYSTEM PUBLISHER, 2025)
This study investigates the impact of digital marketing strategies social media marketing, content marketing, and influencer marketing on consumer behavior in emerging markets, with a focus on Sendys Swalayan in Palangka Raya City, Indonesia. As digital technology increasingly reshapes consumer engagement, businesses in developing regions must understand how strategic online efforts influence customer purchase decisions. Employing a quantitative approach, this study collected data from 44 respondents using structured Likert-scale questionnaires. The data were analyzed using SPSS software, including validity and reliability tests, Pearson correlation, and multiple linear regression. The findings show that all three digital marketing strategies significantly influence consumer purchase decisions, with content marketing having the strongest effect (β = 0.351, p < 0.01), followed by social media marketing (β = 0.284, p < 0.01), and influencer marketing (β = 0.194, p < 0.05). These results indicate that content relevancy and perceived value are key factors that drive consumer interest and action. The study also highlights the importance of authenticity and social interaction in digital spaces, confirming the relevance of theories such as the Elaboration Likelihood Model (ELM) and Source Credibility Theory. This research contributes to the limited literature on localized digital marketing in mid-sized Indonesian cities and offers practical recommendations for retailers aiming to optimize consumer engagement. The study suggests that businesses should prioritize informative, engaging content while leveraging social media and micro-influencer collaborations that align with local cultural values. These strategies are essential for enhancing brand awareness, building trust, and influencing consumer decision-making in the digital era.Keywords: Digital Marketing, Social Media, Content Marketing, Influencer, Consumer Behavior, Purchase Decision, Emerging Markets.